Studying Children's Experiences in Interactions With Clinicians: Identifying Methods Fit for Purpose. (February 2019) - Bryan, Gemma; Bluebond-Langner, Myra; Kelly, Daniel; Kumpunen, Stephanie; Oulton, Kate; Gibson, Faith
Increased emphasis on the child's voice and point of view in care and treatment has led to an expansion in the development of methods to access and identify their perspectives. Drawing on our experiences in a study of children with leukemia in hospital, this article explains the challenges and opportunities that arise in the use of five commonly used methods in a study of hospitalized children's experiences with health care professionals, including the "Draw and Write" technique, a sticker activity, a paper–person exercise, informal interviews, and participant observation. Each of these methods was examined with regard to ease of use, data generation, and utility of data for accessing children's perspectives and development of initial clinical guidance.